Políticas de requalificação urbana na orla marítima do bairro Praia de Iracema: uma avaliação de políticas públicas através da construção de indicadores socioculturais a partir da história oral - Brasil Júnior, José Evanes (2020)
The implementation of urban requalification politics is part of the main actions of the Fortaleza Prefecture, in Praia de Iracema neighborhood. Historically related to bohemia, tourism and leisure, since the 1990s the neighborhood has been the target of these politics that still facing old challenges such as urban violence, drug trafficking, prostitution, real estate speculation, among others.Because the problems refer to the history of the neighborhood, especially through oral narratives that highlight the difficulties of constituting public policies with the participation of civil society groups and the primacy of economic interests under the interventions, this research is an evaluation of public politics from the oral history of people and groups that, over time, practiced the urban space. In an approach that privileges the interpretation of meanings attributed to Praia de Iracema, we highlight some uses and appropriations of space based on the study of interdisciplinary character which permeates or the field of applied social sciences. Therefore, it comprises an evaluation of public politics as a social research, conducted from the dialogue with the different demanding groups. This is because the research permeates the understanding that public policies respond to problems expressed in social demands and, therefore, require the participation of the demanding groups for their constitution and evaluation. Thus, it is necessary to consider the local specificities of the territory and its historicity, approaching cultural issues relevant to the area under intervention. As a result, sociocultural indicators were developed in order to carry out an evaluation of qualitative public policies, considering oral narratives and field insertion work. The importance of dialogue with the different groups for the development of politics capable of responding to local problems was realized. In addition, it was also noticed that the requalification politics can be expanded, acting together with cultural politics for youths, educational actions for heritage and environment, among others. It is noteworthy that the belonging to the urban territories comes from uses and appropriations that refer to a practiced space once that the official limits determined by the state are not always determinant. It was observed that the disputes in the urban space are also symbolic, going through the process of interpretation of public policies by the demanding groups and referring to social conflicts. In this sense, the management and evaluation of public politics should be characterized as capable of dialoguing with various groups and democratizing a city.